Capsule Endoscopy: A Single Centre Experience with the First 226 Capsules - R Enns; K Go; H Chang; K Pluta (Canadian Journal of Gastroenterology, 2004)
BACKGROUND: Capsule endoscopy (CE) refers to a novel diagnostic method of imaging the gastrointestinal tract using a wireless capsule that transmits images to a data recorder while the device traverses the small intestine.